Developing digital marketing : relationship perspectives - Thaichon, Park; Ratten, Vanessa (Emerald Publishing Limited, 2021)
Digital marketing has gained ascendancy as the modern communication method used by most organizations through its ability to transcend geographic restrictions. Developing Digital Marketing: Relationship Perspectives provides a holistic perspective about the role of digital marketing in the global economy. Each chapter offers a different perspective about the importance of digital marketing in the knowledge economy, helping readers to understand the shift from traditional marketing to more novel and innovative forms that are derived from digital marketing functions. Themes explored throughout the book include: Service Encounters via Social Media and Customer Relationships; Digital and Organizational Storytelling; Artificial Intelligence and Customer Experience; Sustainability Project Partnerships. As the nature of these digital practices is evolving Developing Digital Marketing: Relationship Perspectives views the concept of digital marketing as now in constant flux, with the edited chapters paving the way to a better appreciation of how digital marketing is changing particularly through issues such as environmental sustainability in the current business environment.- Resumé vydavatel